Stress-induced cardiomyopathy in the absence of complaints - N. M. Butkevich; K. S. Dolgatova; M. V. Khodyreva; A. A. Gorbachenkov (Klinicist)
Stress-induced cardiomyopathy or Takotsubo cardiomyopathy that generally runs with the clinical manifestations of acute coronary syndrome and left ventricular asynergy, which are caused by emotional, psychological, or physical stress, is most frequently encountered among the unclassified cardiomyopathies. A clinical case of this myocardial lesion without clinical manifestations, but with transient electrocardiographic changes and evident impairment of left ventricular contraction is described.